The Effect of Water-Soluble Polysaccharides from Yam (Pachyrhizus erosus L.) on Mice with Diabetes Mellitus - Sri Rizki Fitri; Herla Rusmarilin; Ridwansyah Ridwansyah (Universitas Sumatera Utara, 2016)
Yam tuber (Pachyrhizus erosus L.) is the kind of tuber that contain the most potential compounds i.e. water-soluble polysaccharide (WSP). The WSP have an ability to degrade blood glucose level. The purpose of this study was to uncover the characteristics of WSP in yam and the effect of of the WSP on the male white mice with diabetes mellitus. The observed parameters on the chemico-pysical charactersitics of the WSP were viscosity, soluble ability, dextrose equivalent, polymerization degree, glucose content, total sugars, reducing sugars, and starch content. In vivo test was using 31 male white mice (aged 2 months) with an average weight of 25-30 g for glucose tolerance test, body weight measure, and the hypoglycaemic effect. The glucose tolerance test concisted 5 of mice and using a Completely Randomize Design (CRD). The blood glucose level was examined periodic at 30 minutes, 60 minutes, 90 minutes, and 120 minutes. The examination of body weight and the hypoglycaemic effect was done for 28 mice using a Completely Randomize Design (CRD) with two factors i.e. the type treatment: the control group (treated with aquadest), the negative group (inducted with streptozotocin 180 mg/kg body weight and treated aquadest), the positive group (treated WSP of 400 mg/kg body weight), and the treatment group (inducted with streptozotocin of 180 mg/kg body weight and treated with WSP of 400 mg/kg body weight) and periodical time of examination: week-1, week-2, week-3, and week-4. Each treatment consisted of 7 mice. Glucose tolerance test showed that the WSP of yam could inhibited glucose absorption in the gastrointestinal. Result of this research showed that the suplementation of yam WSP at 400 mg/kg body weight can significantly decreased blood glucose level and increased body weight (P<0,01) in 4 weeks of streptozotocin induction mice. Keyword: yam, water-soluble polysaccharide, blood-glucose level, diabetes mellitus